Preparation and In Vitro Permeation of Chlopheniramine Maleate (CPM) from Gel through Rat Skin - S. Mahmood, Wissam; A. Kamal, Balkis (Iraqi Journal of Pharmaceutical Sciences, 2017)
Chlopheniramine maleate ( CPM ) , is one of the H- receptor antagonist , widely used in allergic diseases ,like skin rash and pruritis .CPM 3%w/w was successfully loaded in 2%w/w sodium alginate (SA) as a gel base , and to be considered as a selected formula .It was found that the diffusion of CPM through the skin of albino rat was increased as the concentration of CPM increased from 2 %w/w sodium alginate , More over , the addition of Triethanolamine 5 % w/w, to sodium alginate 2 % w/w , loaded by CPM 3 % w/w , enhanced the amount of CPM diffuse through the skin of albino rat . Mean while the addition of PEG 1000 2% w/w , and urea 5 % w/w, separately to sodium alginate 2 % w/w , loaded by CPM 3 % w/w , hindered significantly P<0.05 the amount of the drug diffused through the skin of the rat .The selected formula of sodium alginate 2% w/w as a base loaded by CPM 3% w/w was physically acceptable , with shelf life approximately 3.3 years . Key wards: chlopheniramine maleate , gel , skin permeation